Impact of the Programa Mais médicos (more doctors Programme) on primary care doctor supply and amenable mortality: quasi-experimental study of 5565 Brazilian municipalities - Hone, Thomas (BMC Health Serv Res, 2020)
BACKGROUND: Investing in human resources for health (HRH) is vital for achieving universal health care and the Sustainable Development Goals. The Programa Mais Médicos (PMM) (More Doctors Programme) provided 17,000 doctors, predominantly from Cuba, to work in Brazilian primary care. This study assesses whether PMM doctor allocation to municipalities was consistent with programme criteria and associated impacts on amenable mortality. METHODS: Difference-in-differences regression analysis, exploiting variation in PMM introduction across 5565 municipalities over the period 2008–2017, was employed to examine programme impacts on doctor density and mortality amenable to healthcare. Heterogeneity in effects was explored with respect to doctor allocation criteria and municipal doctor density prior to PMM introduction. RESULTS: After starting in 2013, PMM was associated with an increase in PMM-contracted primary care doctors of 15.1 per 100,000 population. However, largescale substitution of existing primary care doctors resulting in a net increase of only 5.7 per 100,000. Increases in both PMM and total primary care doctors were lower in priority municipalities due to lower allocation of PMM doctors and greater substitution effects. The PMM led to amenable mortality reductions of − 1.06 per 100,000 (95%CI: − 1.78 to − 0.34) annually – with greater benefits in municipalities prioritised for doctor allocation and where doctor density was low before programme implementation. CONCLUSIONS: PMM potential health benefits were undermined due to widespread allocation of doctors to non-priority areas and local substitution effects. Policies seeking to strengthen HRH should develop and implement needs-based criteria for resource allocation.